Research on the mechanical properties and microstructure of saline soil subgrade improved by steel slag powder and lime - Liu, Peirong; Long, Shiyu; Huang, Zhenping; Shen, Xin; Li, Guodong; Su, Jinghong; Zhu, Jie (Frontiers in Materials, 2026)
Saline soils typically exhibit poor engineering properties, including low strength and instability, which severely compromising the structural stability of subgrade in arid and semi-arid regions. Based on this, a method for improving subgrade in saline soil areas using a composite of steel slag powder and lime was proposed in this study. Through orthogonal experimental design, the effects of total content, steel slag proportion, moisture content, and curing age on the unconfined compressive strength of saline soil were systematically analysed. Shear performance parameters of the modified soil were obtained in conjunction with direct shear tests. The mechanism of modification was elucidated using Scanning Electron Microscope-Energy Dispersive Spectroscopy (SEM-EDS) and X-ray Diffraction (XRD). The results indicate that the optimal improvement scheme is a total admixture content of 15% (comprising 75% steel slag and 25% lime), the moisture content is 4.48%, and the curing age is 28 days. At this point, the unconfined compressive strength reached 403.50 kPa, approximately 3.8 times that of the unmodified soil; the cohesion increased significantly from 11.8 kPa to 54.2 kPa, while the angle of internal friction showed no significant change. Microstructural analysis indicates that the composite modification of steel slag powder and lime generates calcium silicate hydrate gel and calcium carbonate, significantly reducing the porosity of saline soil. This enhances intergranular bonding, resulting in a more compact and stable structure. The study has validated the high efficiency and sustainability of this method, providing reliable technical support for the remediation of subgrade defects in road engineering projects within saline soil regions.